Estimulación del lenguaje en la educación infantil - Herrera Riera, Paulina Alejandra (2019)
The present research project was carried out with the objective of stimulating the language through playful practices for the socialization of the infants of the Child Development Center "Niño de Isinche" to contribute to the integral child development. Considering that the development of language in early childhood can be directly affected by poor stimulation both in the educational environment and in the family. The Niño Infant Development Center of Isinche, is located in the Pujilí canton of the province of Cotopaxi, belongs to the Board of Social Welfare of the Autonomous Decentralized Government of Pujilí canton and houses 60 children from 1 to 3 years, who make up the beneficiaries of the research together with the 6 educators, the coordinator and the 60 parents. The methodology applied in the development of the research had a qualitative and quantitative approach, combined with a bibliographic and field design, through the application of the interview to the coordinator and a child language specialist, the survey of educators and parents of family and direct observation of the level of development of children's language from the indicators exposed in the theoretical foundation. The impact reached by the research is of a social and educational nature aimed at improving language stimulation practices in the children's center and in the home. The results of the research reaffirm the existence of cases of children with delayed language development, because they do not meet the indicated indicators, educators do not have teaching materials and innovative strategies to stimulate language development from the early years of life.